Prevalence of caries and related factors in patients with cystic fibrosis (Research, Society and Development, 2021)
Cystic fibrosis (CF) is an autosomal recessive, lethal disease, more common in Caucasians and prevalent in both sexes. More than 1000 mutations are known, the most common being Delta-F508, which is the alteration of RTF protein synthesis (cystic fibrosis transmembrane conductance regulatory protein), affecting cells of various organs, especially those of the respiratory tract, which are related to main deleterious effects, causing death in more than 90% of patients, due to impairment of the functioning of the exocrine glands that produce thicker substances, thus hindering their elimination. Aiming to assess the prevalence of caries and related factors in a group of 20 children with cystic fibrosis, aged from 01 to 14 years of age, and to correlate data from the dental questionnaire with information collected from clinical examinations performed. This work is a descriptive, analytical case-control study with a cross-sectional design. To analyze the data obtained, the Shapiro-Wilks, Student's T, Mann-Whitney, ANOVA and Poisson tests were used. For all tests, a statistical significance level of 5% (p